The effect of different fermentation medium on quality of fermented common snake head (channa striata) Bekasam - Sari, N Ira (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was intended to evaluate the quality of fermented snake head using different fermentation starter. The fish weighting 800-1000 each was eviscerated, washed and salted at a level of 30% for 48 hours. The fish then was added with roasted rice flour at a level of 50% of fish weight. The mixture then grouped into 3 groups (500g/group) and each group was added respectively with 25% of a liquid of fermented bamboo shoot (B2), 25% phyloric caeca (B3) and withant medium (B1). The mixture was fermented for 7 days. The fermented fish was evaluated for sensory quality, pH and lactie acid bacteria count. The result showed that the quality of fermented snake head added with phyloric caeca (B3) was the best in sensory quality. pH and lactie acid bacteria count of the fermented fish at the end of fermentation was 5,48 and 4,9 x 105 cell/gram respectively for (B1), 4,94 and 28,51 x 105 cell/gram respectively for (B2) and 4,72 and 62,57 x 105 cell/gram respectively for (B3).Kata kunci: Channa striata, bekasam, bamboo shoot, phyloric caeca,